A deep investigation into the structure of carbon dots. (March 2021) - Mintz, Keenan J.; Bartoli, Mattia; Rovere, Massimo; Zhou, Yiqun; Hettiarachchi, Sajini D.; Paudyal, Suraj; Chen, Jiuyan; Domena, Justin B.; Liyanage, Piumi Y.; Sampson, Rachel; Khadka, Durga; Pandey, Raja R.; et al.
Abstract: Since their discovery, carbon dots (CDs) have been a promising nanomaterial in a variety of fields including nanomedicine. Despite their potential in this area, there are many obstacles to overcome for CDs to be approved for biomedical use. One major hindrance to CDs' approval is related to their poorly defined structure. Herein a structural study of CDs is presented in order to rectify this shortcoming. The properties of three CDs which have significant promise in biomedical applications, black CDs (B-CDs), carbon nitride dots (CNDs), and yellow CDs (Y-CDs), are compared in order to develop a coherent structural model for each nanosystem. Absorption coefficients were measured for each system and this data gave insight on the level of disorder in each system. Furthermore, extensive structural characterization has been performed in order to derive structural information for each system. This data showed that B-CDs and CNDs are functionalized to a greater degree and are also more disordered and amorphous than Y-CDs. These techniques were used to develop a structural model consistent with the obtained data and what is known for carbonic nanostructures. These models can be used to analyze CD emission properties and to better understand the structure-property relationship in CDs. Graphical abstract: This graphic illustrates the stark distinction in properties between certain carbon dots (CDs). This work highlights the large diversity of properties among CDs and endeavors to go beyond the spherical shape typically associated with this material to see the core structure and understand the formation of CDs. Image 1